Hard alloy and preparation method and application thereof
By using (W,Re)C hard phase and Ru/Os, Co, Re composite bonding phases added in cemented carbide, and uniformly dissolve elements through pre-ball milling and ball milling processes, the problem of failure of existing cemented carbide in cutting processing is solved, and the comprehensive improvement of high hardness, high toughness and high temperature performance is achieved.
Patent Information
- Application Number
- CN202411706242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Existing cemented carbide materials are prone to wear and collapse during cutting and processing, and the single addition of Ru or Re has limitations on performance improvement, making it difficult to improve hardness, strength and high-temperature performance at the same time.
The cemented carbide containing the (W,Re)C hard phase and the bonding phase added by Ru/Os, Co, Re is used to uniformly dissolve Ru and Os in the bonding phase through pre-ball milling and ball milling processes. Re is mainly dissolved in the hard phase WC, and the proportion of elements in the alloy and process parameters are reasonably controlled.
It realizes the high hardness, high toughness and good high temperature performance of cemented carbide, and is suitable for cutting and processing of difficult-to-process materials and stainless steel materials, and the preparation process is stable and convenient for industrial production.
Smart Images

Figure CN119530628A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a cemented carbide and a preparation method and application thereof. Background Art
[0002] In the cutting process, the common failure forms of cemented carbide tools are wear and chipping, and the failure reasons are low hardness and low strength of the tool material. In conventional cemented carbide material systems, the hardness of the alloy must be improved at the expense of the alloy strength, and vice versa. Therefore, how to simultaneously improve the hardness and strength of the material has always been the research focus of material researchers, and it is also an existing problem that needs to be solved urgently. Patent documents CN1088116C and CN104404337A improve the mechanical properties of cemented carbide by adding Ru elements, and patent document CN111321334B improves the wear resistance and high temperature performance of cemented carbide by adding Re elements. However, with the rapid development of science and technology, new material technology is changing our world. New materials have been widely used in aerospace, new energy, biomedicine and other fields. These new materials surpass traditional materials in performance, such as high strength, light weight, and oxidation resistance. However, the machinability of metal parts made of new materials is getting lower and lower, and the requirements for cemented carbide tools are getting higher and higher. The single addition of Ru and Re elements has limitations on the performance improvement of cemented carbide. Therefore, it is urgent to develop cemented carbide with better comprehensive performance. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a cemented carbide having high hardness, high toughness and good high temperature performance, stable preparation process and convenient industrial production, as well as a preparation method and application thereof.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0005] A cemented carbide comprises a hard phase and a binder phase, wherein the hard phase is (W, Re)C, the components of the binder phase include one or two of Ru and Os, Co and Re, the mass of Re dissolved in the hard phase accounts for 50% to 90% of the total mass of Re in the cemented carbide, and the atomic percentage of total Re / Co in the cemented carbide is not greater than 25%.
[0006] The above-mentioned cemented carbide, preferably, has a total Re / W atomic percentage of not less than 1.3%.
[0007] For the above-mentioned cemented carbide, preferably, 3%≤the total atomic percentage of Re / Co≤15%, and 1.3%≤the total atomic percentage of Re / W≤7.2%.
[0008] As a general technical concept, the present invention also provides a method for preparing the above-mentioned cemented carbide, comprising the following steps:
[0009] (1) Ingredients: M alloy powder, tungsten-rhenium alloy powder, WC powder and carbon powder are used as raw materials, wherein the M alloy powder is one or both of cobalt-ruthenium alloy powder and cobalt-osmium alloy powder. Taking the total amount of raw materials as 100%, by mass fraction, when the M alloy powder is cobalt-ruthenium alloy powder, the cobalt-ruthenium alloy powder is 5.5% to 18.0%, when the M alloy powder is cobalt-osmium alloy powder, the cobalt-osmium alloy powder is 5.8% to 19.7%, when the M alloy powder is cobalt-ruthenium alloy powder and cobalt-osmium alloy powder, the sum of the cobalt-ruthenium alloy powder and the cobalt-osmium alloy powder is 5.6% to 19.5%, the tungsten-rhenium alloy powder is 4.0% to 23.0%, the addition amount of the tungsten-rhenium alloy powder should follow the principle that the atomic percentage of total Re / Co in the cemented carbide is not greater than 25%, and the addition amount of the carbon powder is m C =(0.0653m W +0.0496m Re )×x, x=0.85~1.00, m C is the mass of toner, m W 、m Re are the masses of tungsten and rhenium in tungsten-rhenium alloy powder, respectively, and WC powder is the remainder;
[0010] (2) The raw materials are pre-milled and then ball-milled, and the resulting mixture is dried, granulated, molded and sintered to obtain a cemented carbide.
[0011] In the above-mentioned method for preparing cemented carbide, preferably, in step (1), the atomic percentage of Ru in the cobalt-ruthenium alloy powder is 5% to 30%, the atomic percentage of Os in the cobalt-osmium alloy powder is 3% to 20%, and 20%≤the mass fraction of Re in the tungsten-rhenium alloy powder≤26%.
[0012] In the above-mentioned method for preparing cemented carbide, preferably, in step (2), the specific process of the pre-milling and ball milling is as follows: the raw materials except WC powder are mixed, and pre-milled until the Fsss particle size of the powder is ≤1μm, and then WC powder is added for ball milling.
[0013] In the above-mentioned method for preparing cemented carbide, preferably, in step (2), the pre-milling time is 5h to 30h, and the ball milling time is 20h to 50h.
[0014] In the above-mentioned method for preparing cemented carbide, preferably, in step (1), the purity of the cobalt-ruthenium alloy powder is not less than 99.90%, and the Fsss particle size of the cobalt-ruthenium alloy powder is ≤5μm; the purity of the cobalt-osmium alloy powder is not less than 99.90%, and the Fsss particle size of the cobalt-osmium alloy powder is ≤5μm; the purity of the tungsten-rhenium alloy powder is not less than 99.90%, and the Fsss particle size of the tungsten-rhenium alloy powder is ≤10μm.
[0015] In the above-mentioned method for preparing cemented carbide, preferably, in step (1), the Fsss particle size of the WC powder is 0.5 μm to 5.0 μm.
[0016] In the above-mentioned method for preparing cemented carbide, preferably, in step (1), the raw material further comprises nitride powder or carbide powder of one or more of Ta, Nb and Ti.
[0017] In the above-mentioned method for preparing cemented carbide, preferably, in step (1), the raw material also includes an inhibitor, and the inhibitor includes Cr3C2 powder and / or VC powder, wherein the Cr content satisfies a Cr / Co mass ratio of 0 to 10.0%, and the V content satisfies a V / Co mass ratio of 0 to 4.0%.
[0018] In the above-mentioned method for preparing cemented carbide, preferably, in step (2), the molding agent used for molding is a mixture of PEG4000 and PEG1500 or PEG4000, and the mass of the molding agent is 2% to 3% of the mass of the mixture. When the molding agent is a mixture of PEG4000 and PEG1500, the mass of the PEG1500 is 0.5% of the mass of the mixture;
[0019] The sintering is vacuum sintering or high-pressure sintering, and the sintering temperature is 1400° C. to 1550° C. When the sintering is high-pressure sintering, the protective atmosphere used is argon atmosphere, and the pressure of the high-pressure sintering is 40 bar to 80 bar.
[0020] As a general technical concept, the present invention also provides an application of the above-mentioned cemented carbide or the cemented carbide prepared by the above-mentioned preparation method in the preparation of cemented carbide cutting tools.
[0021] In the present invention, the mass fraction of impurities in the raw material of cemented carbide is less than 0.01%.
[0022] In the present invention, the cemented carbide has high hardness, high toughness and good high temperature performance, can be applied to cemented carbide tools, and can be suitable for continuous and intermittent cutting of difficult-to-cut materials and stainless steel materials.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] 1. According to the applicant's research, Ru and Os have a solid solution strengthening effect on the cobalt phase, which can improve the impact toughness of the cemented carbide. Re has a solid solution strengthening effect on WC, which can improve the wear resistance and high temperature performance of the cemented carbide. The present invention adopts Ru / Os and Re composite addition, which can have a solid solution strengthening effect on the bonding phase and hard phase WC of the cemented carbide, synergistically strengthen the cemented carbide structure, and can simultaneously improve the hardness, toughness, fatigue performance and high temperature performance of the cemented carbide.
[0025] In order to solve the problem of uneven distribution of Ru and / or Os and Re in cemented carbide, the present invention uses cobalt-ruthenium alloy powder and / or cobalt-osmium alloy powder and tungsten-rhenium alloy powder as raw materials, combined with a pre-ball milling process, so that Ru and / or Os are uniformly dissolved in the binder phase Co, and more Re is dissolved in the hard phase WC, so as to obtain a cemented carbide with a uniform structure. In addition, since ruthenium and / or osmium elements are dissolved in the binder phase cobalt, the content of rhenium in the cobalt phase will be reduced, so that more Re is dissolved in WC, further strengthening the solid solution strengthening effect of the Re element on the hard phase WC.
[0026] The present invention adds composite alloy powder to cemented carbide and limits the amount of alloy powder added and the ratio of Ru and / or Os to Re in the alloy, so that the cemented carbide has good comprehensive mechanical properties and is suitable for cemented carbide cutting tools, and can meet the requirements of continuous and intermittent cutting of difficult-to-process materials and stainless steel materials under various working conditions.
[0027] 2. In actual production and application, the cemented carbide of the present invention can be produced and prepared by a powder metallurgy method, and the preparation process is stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the transmission electron microscope element distribution diagram of the cemented carbide of comparative example 1.
[0029] Figure 2 This is the transmission electron microscope element distribution diagram of the cemented carbide of Comparative Example 2.
[0030] Figure 3 This is the transmission electron microscope element distribution diagram of the cemented carbide of comparative example 3.
[0031] Figure 4 TEM element distribution diagram of the cemented carbide of Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.
[0033] Example 1
[0034] A cemented carbide of the present invention comprises a hard phase and a binder phase, wherein the hard phase is (W, Re)C, the components of the binder phase include Ru, Co and Re, the mass of Re dissolved in the hard phase accounts for 61% of the total mass of Re in the cemented carbide, the atomic percentage of total Re / Co in the cemented carbide is 4.74 at.%, and the atomic percentage of total Re / W is 1.84 at.%.
[0035] A method for preparing a cemented carbide according to the present invention comprises the following steps:
[0036] (1) Ingredients: M alloy powder, tungsten-rhenium alloy powder, WC powder and carbon powder are used as raw materials. M alloy powder is cobalt-ruthenium alloy powder. The total amount of raw materials is 100%. By mass fraction, the cobalt-ruthenium alloy powder is 12.50wt%, the tungsten-rhenium alloy powder is 6.10wt.%, and the amount of carbon powder added is m C =(0.0653m W +0.0496m Re )×x,x=0.92,m C is the mass of toner, m W 、m Re are the masses of tungsten and rhenium in tungsten-rhenium alloy powder, respectively. The mass fraction of carbon powder corresponding to the mass of carbon powder is 0.62wt.%, and WC powder is the remainder (80.78wt.%);
[0037] In this embodiment, the atomic percentage of Ru in the cobalt-ruthenium alloy powder is 12.7%, the purity of the cobalt-ruthenium alloy powder is 99.94%, and the Fsss particle size is 2.0 μm.
[0038] In this embodiment, the mass fraction of Re in the tungsten-rhenium alloy powder is 24.6%, the purity of the tungsten-rhenium alloy powder is 99.92%, and the Fsss particle size is 3.5 μm.
[0039] In this embodiment, the Fsss particle size of the WC powder is 3.2 μm.
[0040] (2) Add a ball mill rod, cobalt-ruthenium alloy powder, tungsten-rhenium alloy powder, carbon powder, a molding agent and anhydrous alcohol to a wet grinder, pre-ball mill for 15 hours until the Fsss particle size of the powder is 0.9 μm, then add WC powder, and continue wet milling for 25 hours to obtain a mixture, wherein the ball-to-material ratio (the mass ratio of the ball mill rod to all raw materials) is 10:1, spray dry the mixture, granulate it, and press it into a molding agent, wherein the molding agent is PEG4000, and the mass of the molding agent is 2.0% of the mass of the mixture, and high-pressure sintering is carried out at 1450°C in an argon atmosphere for 30 minutes, and the pressure of the argon atmosphere is 60 bar. After sintering, a cemented carbide is obtained.
[0041] Comparative Example 1
[0042] A cemented carbide, the raw material composition and mass fraction are: WC powder 90.00wt.%, Fsss particle size 3.2μm, cobalt powder 10.00wt.%, Fsss particle size 1.0μm. The preparation process is the same as that of Example 1.
[0043] Comparative Example 2
[0044] A cemented carbide, the raw material composition and mass fraction are: WC powder 88.38wt.%, Fsss particle size 3.2μm, cobalt powder 10.00wt.%, Fsss particle size 1.0μm, Re powder 1.55wt.%, Fsss particle size 1.5μm, carbon powder 0.07%. The preparation process is the same as that of Example 1. The total Re / W atomic ratio of Comparative Example 2 and Example 1 is 1.84at.%.
[0045] Comparative Example 3
[0046] A cemented carbide, the raw material composition and mass fraction are: WC powder 87.50wt.%, Fsss particle size 3.2μm, cobalt powder 10.00wt.%, Fsss particle size 1.0μm, Ru powder 2.50wt.%, Fsss particle size 2.0μm. The preparation process is the same as that of Example 1. The atomic percentage of Ru / Co in Comparative Example 3 and Example 1 is both 12.7at.%.
[0047] Table 1 Mechanical properties of cemented carbides of Example 1 and Comparative Examples 1-3
[0048] Mechanical properties Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Hardness (Hv3) 1390 1280 1370 1320 <![CDATA[Flexural strength TRS (N / mm 2 )]]> 3264 2440 2380 3150 High temperature hardness (Hv10, 800℃) 1020 780 950 920 Fatigue performance (bending times, 10,000 times) 44 15 19 24 Fatigue performance (average bending strength, kN) 26 20 22 22
[0049] It can be seen from Table 1 that, compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, the cemented carbide of Example 1 has higher hardness, bending strength, high temperature hardness and fatigue performance. It can be seen that the cemented carbide of the present invention exhibits very high comprehensive mechanical properties.
[0050] The transmission electron microscopy element distribution of the cemented carbide of comparative example 1 is shown in Figure 1 The main elements of the hard phase are W and C, and the main element of the bonding phase is Co.
[0051] The transmission electron microscopy element distribution of the cemented carbide of comparative example 2 is shown in Figure 2 , metal Re is solid dissolved in the hard phase WC.
[0052] The transmission electron microscopy element distribution of the cemented carbide of comparative example 3 is shown in Figure 3 , metal Ru is solid dissolved in the binder phase Co.
[0053] The transmission electron microscopy element distribution of the cemented carbide of Example 1 is shown in Figure 4 , metal Ru is solid dissolved in the binder phase Co, and metal Re is mainly solid dissolved in the hard phase WC.
[0054] RCKT1204M0-NM milling inserts were prepared using the cemented carbides of Example 1 and Comparative Examples 1, 2 and 3, and a milling comparison test of stainless steel 1Cr18Ni9Ti was performed. The cutting parameters are shown in Table 2 below.
[0055] Table 2 Milling comparison test parameters
[0056] speed Feed Depth of cut Cutting width Cooling method 240m / min 0.15mm / r 3.0mm 30mm Coolant
[0057] It can be seen from Table 3 that, compared with the cemented carbide tools of Comparative Examples 1, 2 and 3, the cemented carbide tool produced in Example 1 of the present invention exhibits a better cutting life.
[0058] Table 3 Milling comparison test results
[0059] Blade 1 No. 2 Blade 3 Blade 4 Example 1 130min 138min 126min 131min Comparative Example 1 65min 48min 58min 60min Comparative Example 2 82min 110min 90min 75min Comparative Example 3 94min 95min 104min 99min
[0060] Example 2
[0061] A cemented carbide of the present invention comprises a hard phase and a binder phase, wherein the hard phase is (W, Re)C, the components of the binder phase include Os, Co and Re, the mass of Re dissolved in the hard phase accounts for 66% of the total mass of Re in the cemented carbide, the atomic percentage of total Re / Co in the cemented carbide is 6.33 at.%, the atomic percentage of total Re / W is 1.64 at.%, and the Cr / Co mass ratio is 0.2 wt.%.
[0062] A method for preparing a cemented carbide according to the present invention comprises the following steps:
[0063] (1) Ingredients: M alloy powder, cobalt-osmium alloy powder, WC powder, carbon powder, TaNbC powder and Cr3C2 powder are used as raw materials. M alloy powder is cobalt-osmium alloy powder. The total amount of raw materials is 100%. By mass fraction, the cobalt-osmium alloy powder is 8.37wt.%, the tungsten-rhenium alloy powder is 5.65wt.%, and the added amount of carbon powder is m. C =(0.0653m W +0.0496m Re )×x,x=0.90,m C is the mass of toner, m W 、m Re are the masses of tungsten and rhenium in tungsten-rhenium alloy powder respectively. The mass fraction of carbon powder corresponding to the mass of carbon powder is 0.60wt.%, TaNbC powder is 0.76wt.%, Cr3C2 powder is 0.16wt.%, and WC powder is the remainder (84.46wt.%).
[0064] In this embodiment, the atomic percentage of Os in the cobalt-osmium alloy powder is 6.0%, the purity of the cobalt-osmium alloy powder is 99.90%, and the Fsss particle size is 3.0 μm.
[0065] In this embodiment, the mass fraction of Re in the tungsten-rhenium alloy powder is 24.6%, the purity of the tungsten-rhenium alloy powder is 99.92%, and the Fsss particle size is 3.5 μm.
[0066] In this embodiment, the Fsss particle size of the WC powder is 0.68 μm, the Fsss particle size of the TaNbC powder is 2.1 μm, and the Fsss particle size of the Cr3C2 powder is 1.2 μm.
[0067] (2) Add a ball mill rod, cobalt-osmium alloy powder, tungsten-rhenium alloy powder, carbon powder, TaNbC powder, Cr3C2 powder, a molding agent and anhydrous alcohol to a wet grinder, pre-ball mill for 15 hours until the Fsss particle size of the powder is 0.8 μm, then add WC powder, and continue wet milling for 40 hours to obtain a mixture, wherein the ball-to-material ratio is 10:1; spray dry the mixture, granulate it, and press it into a molding agent, wherein the molding agent is PEG4000 and PEG1500, and the mass of the two is 2.0% and 0.5% of the mass of the mixture, respectively; sinter under high pressure at 1420°C in an argon atmosphere for 30 minutes, and the pressure of the argon atmosphere is 60 bar. After sintering, a cemented carbide is obtained.
[0068] Comparative Example 4
[0069] A cemented carbide, the raw material composition and mass fraction are: WC powder 92.08wt.%, Fsss particle size 0.68μm, TaNbC powder 0.76wt.%, cobalt powder 7.00wt.%, Fsss particle size 1.0μm, Cr3C2 powder 0.16wt.%, Fsss particle size 1.2μm. The preparation process is the same as that of Example 2.
[0070] Comparative Example 5
[0071] A cemented carbide, the raw material components and their mass fractions are: WC powder 90.57wt.%, Fsss particle size 0.68μm, TaNbC powder 0.76wt.%, cobalt powder 7.00wt.%, Fsss particle size 1.0μm, Re powder 1.41wt.%, Fsss particle size 1.5μm, Cr3C2 powder 0.16wt.%, Fsss particle size 1.2μm, carbon powder addition amount 0.10wt.%, the preparation process is the same as that of Example 2. The total Re / W atomic percentage in Comparative Example 5 and Example 2 is 1.64at.%.
[0072] Comparative Example 6
[0073] A cemented carbide, the raw material components and their mass fractions are: WC powder 90.62wt.%, Fsss particle size 0.68μm, TaNbC powder 0.76wt.%, cobalt powder 7.00wt.%, Fsss particle size 1.0μm, Os powder 1.42wt.%, Fsss particle size 3.0μm, Cr3C2 powder 0.16wt.%, Fsss particle size 1.2μm, carbon powder addition amount 0.04wt.%, and the preparation process is the same as that of Example 2. The atomic percentage content of Os / Co in Comparative Example 6 and Example 2 is 6at.%.
[0074] Table 4 Mechanical properties of cemented carbides of Example 2 and Comparative Examples 4-6
[0075] Mechanical properties Example 2 Comparative Example 4 Comparative Example 5 Comparative Example 6 Hardness (Hv3) 1760 1650 1720 1700 <![CDATA[Flexural strength TRS (N / mm 2 )]]> 2844 2247 2150 2752 High temperature hardness (Hv10, 800℃) 1390 980 1230 1150 Fatigue performance (bending times, 10,000 times) 22 14 16 17 Fatigue performance (average bending strength, kN) 18 12 15 14
[0076] It can be seen from Table 4 that, compared with Comparative Examples 4, 5, and 6, the cemented carbide of Example 2 has higher hardness, strength, high temperature hardness, and fatigue performance, indicating that the cemented carbide of Example 2 of the present invention exhibits better comprehensive mechanical properties.
[0077] The hard alloy prepared in this embodiment is used to prepare hard alloy turning tools. The hard alloys of embodiment 2 and comparative examples 4, 5 and 6 are used to prepare SNMG120412-SNR turning inserts, and the nickel-based high temperature alloy GH4169 is subjected to a comparative turning test. The cutting parameters are shown in Table 5 below.
[0078] Table 5 Parameters of turning comparison test
[0079] speed Feed Depth of cut Cooling method 45m / min 0.15mm / r 1.5mm Coolant
[0080] In the cutting test, the criterion for judging tool failure is that the tool back face wear reaches 0.3 μm or the cutting edge is chipped. It can be seen from Table 6 that compared with the cemented carbide tools of Comparative Examples 4, 5 and 6, the cemented carbide tools produced in Example 2 of the present invention show better cutting life.
[0081] Table 6 Test results of turning comparison test
[0082] time Wear value Example 2 45min 0.29μm Comparative Example 4 28min 0.35μm Comparative Example 5 36min chipping edge Comparative Example 6 35min 0.32μm
[0083] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A cemented carbide, characterized in that: The invention comprises a hard phase and a bonding phase, wherein the hard phase is (W, Re) C, the components of the bonding phase include one or two of Ru and Os, Co and Re, the mass of Re dissolved in the hard phase accounts for 50% to 90% of the total mass of Re in the cemented carbide, and the atomic percentage of total Re / Co in the cemented carbide is not greater than 25%.
2. The cemented carbide according to claim 1, characterized in that: The atomic percentage of total Re / W in the cemented carbide is not less than 1.3%.
3. The cemented carbide according to claim 2, characterized in that: 3%≤the atomic percentage of the total Re / Co≤15%, and 1.3%≤the atomic percentage of the total Re / W≤7.2%.
4. A method for preparing a cemented carbide according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Ingredients: M alloy powder, tungsten-rhenium alloy powder, WC powder and carbon powder are used as raw materials, wherein the M alloy powder is one or both of cobalt-ruthenium alloy powder and cobalt-osmium alloy powder. Taking the total amount of raw materials as 100%, by mass fraction, when the M alloy powder is cobalt-ruthenium alloy powder, the cobalt-ruthenium alloy powder is 5.5% to 18.0%, when the M alloy powder is cobalt-osmium alloy powder, the cobalt-osmium alloy powder is 5.8% to 19.7%, when the M alloy powder is cobalt-ruthenium alloy powder and cobalt-osmium alloy powder, the sum of the cobalt-ruthenium alloy powder and the cobalt-osmium alloy powder is 5.6% to 19.5%, the tungsten-rhenium alloy powder is 4.0% to 23.0%, the addition amount of the tungsten-rhenium alloy powder should follow the principle that the atomic percentage of total Re / Co in the cemented carbide is not greater than 25%, and the addition amount of the carbon powder is m C =(0.0653m W +0.0496m Re )×x, x=0.85~1.00, m C is the mass of toner, m W 、m Re are the masses of tungsten and rhenium in tungsten-rhenium alloy powder, respectively, and WC powder is the remainder; (2) The raw materials are pre-milled and then ball-milled, and the resulting mixture is dried, granulated, molded and sintered to obtain a cemented carbide.
5. The method for preparing cemented carbide according to claim 4, characterized in that: In step (1), the atomic percentage of Ru in the cobalt-ruthenium alloy powder is 5% to 30%, the atomic percentage of Os in the cobalt-osmium alloy powder is 3% to 20%, and 20%≤the mass fraction of Re in the tungsten-rhenium alloy powder≤26%.
6. The method for preparing cemented carbide according to claim 4, characterized in that: In step (2), the specific process of the pre-ball milling and ball milling is as follows: the raw materials except the WC powder are mixed, and pre-ball milled until the Fsss particle size of the powder is ≤1 μm, and then the WC powder is added for ball milling.
7. The method for preparing cemented carbide according to claim 6, characterized in that: In step (2), the pre-ball milling time is 5 h to 30 h, and the ball milling time is 20 h to 50 h.
8. The method for preparing a cemented carbide according to any one of claims 4 to 7, characterized in that: In step (1), the purity of the cobalt-ruthenium alloy powder is not less than 99.90%, and the Fsss particle size of the cobalt-ruthenium alloy powder is ≤5 μm; the purity of the cobalt-osmium alloy powder is not less than 99.90%, and the Fsss particle size of the cobalt-osmium alloy powder is ≤5 μm; the purity of the tungsten-rhenium alloy powder is not less than 99.90%, and the Fsss particle size of the tungsten-rhenium alloy powder is ≤10 μm.
9. The method for preparing a cemented carbide according to any one of claims 4 to 7, characterized in that: In step (1), the Fsss particle size of the WC powder is 0.5 μm to 5.0 μm.
10. The method for preparing a cemented carbide according to any one of claims 4 to 7, characterized in that: In step (1), the raw material further includes nitride powder or carbide powder of one or more of Ta, Nb and Ti.
11. The method for preparing a cemented carbide according to any one of claims 4 to 7, characterized in that: In step (1), the raw material also includes an inhibitor, and the inhibitor includes Cr3C2 powder and / or VC powder, wherein the Cr content satisfies a Cr / Co mass ratio of 0 to 10.0%, and the V content satisfies a V / Co mass ratio of 0 to 4.0%.
12. The method for preparing a cemented carbide according to any one of claims 4 to 7, characterized in that: In step (2), the molding agent used for molding is a mixture of PEG4000 and PEG1500 or PEG4000, and the mass of the molding agent is 2% to 3% of the mass of the mixture. When the molding agent is a mixture of PEG4000 and PEG1500, the mass of the PEG1500 is 0.5% of the mass of the mixture; The sintering is vacuum sintering or high-pressure sintering, and the sintering temperature is 1400° C. to 1550° C. When the sintering is high-pressure sintering, the protective atmosphere used is argon atmosphere, and the pressure of the high-pressure sintering is 40 bar to 80 bar.
13. Use of the cemented carbide according to any one of claims 1 to 3 or the cemented carbide prepared by the preparation method according to any one of claims 4 to 12 in preparing cemented carbide tools.
Citation Information
Patent Citations
Hard alloy and preparation method thereof
CN104404337A
Tool for drilling / routing of printed circuit board materials
CN1088116C
A corrosion-resistant cemented carbide and its application in the manufacture of engineered wood panel saws
CN111321334B
Hard alloy and preparation method thereof
CN117701968A
Cubic boron nitride-containing hard member and its production
JP2000328170A